Effectiveness and mechanism of action of rTMS combined with quadriceps strength training in individuals with knee osteoarthritis: study protocol for a randomized controlled trial - Ming-Hui Lai; Hai-Chen Xu; Yu-Wu Ding; Kun Yang; Xue-Ping Xu; Li-Ming Jiang (BMC Musculoskeletal Disorders, 2024)
Abstract Background Quadriceps training is necessary in function and activity of daily living for patients with knee osteoarthritis (KOA). However, it did not reduce the rate of surgical treatment for end-stage KOA in the long term. This may be related to brain structure changes and maladaptive plasticity in KOA patients. Transcranial Magnetic Stimulation (TMS) could enhance the functional connectivity of brain regions and improves maladaptive plasticity. However, the synergistic effect of the combination of the two for treat KOA is still unclear. Therefore, the purpose of this study is to investigate whether the High-Frequency rTMS combined with quadriceps strength training can improve the pain and function in KOA more effectively than quadriceps training alone and explore the mechanism of action. Methods This study is an assessor-blind, sham-controlled, randomized controlled trial involving 12 weeks of intervention and 6 months follow-up. 148 participants with KOA will receive usual care management and be randomized into four subgroups equally, including quadriceps strength training, high-frequency rTMS training, sham rTMS and quadriceps strength training, high-frequency rTMS and quadriceps strength training. The rehabilitation interventions will be carried out 5 days per week for a total of 12 weeks. All outcomes will be measured at baseline, 4 weeks, 8 weeks, and 12 weeks during the intervention and 1 month, 3 months and 6 months during the follow-up period. The effectiveness outcomes will be included visual analog scale, isokinetic knee muscle strength, Knee Injury and Osteoarthritis Outcome score and 36-Item Short-Form Health Survey score; The act mechanism outcomes will be included motor evoked potential, grey matter density, white matter, subcortical nuclei volumes, cortical thickness and functional connectivity by MRI. Two-way of variance with repeated measures will be used to test the group and time effect for outcome measures. Discussion The study will be the first protocol to examine whether there are synergistic effects following high-frequency rTMS combined with quadriceps strength training for treat KOA and clarify the mechanism of action. High-frequency rTMS can be added into the training program for KOA patients if it is proven effective. Trial registration Chinese Clinical Trial Registry ChiCTR2300067617. Registered on Jan.13,2023.